PENGGUNAAN SARANA DAN PRASARANA UNIT KEGIATAN MAHASISWA PECINTA ALAM DALAM MENINGKATKAN PRESTASI NON-AKADEMIK MAHASISWA UNIVERSITAS COKROAMINOTO YOGYAKARTA - Nurarifah, Lely; Machali, Imam; Musakal, Musakal; Agryanda, Agryanda (Gemi: Jurnal Penelitian dan Pengabdian, 2023)
This research was conducted to determine the use and utilization of facilities and infrastructure in supporting the non-academic achievements of students who enter and become members of Mapala Unisco. This research will discuss about: a) how the facilities and infrastructure of Mapala Unisco; b) how to utilize the facilities and infrastructure of Mapala Unisco; and c) how the impact of Mapala Unisco facilities and infrastructure in improving non-academic achievement. The method used in this study is descriptive qualitative. The facilities and infrastructure owned by Mapala Unisco are used to carry out four divisions: rock climbing, rafting, caving, and mountain forest. The lack of complete tools is owned, making the maximum achievement obtained by Mapala Unisco.